Respuesta :

Answer:

D

Step-by-step explanation:

Given

4x² - 13x + 3

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term

product = 4 × 3 = 12 and sum = - 13

The factors are - 12 and - 1

Use these factors to split the x- term

4x² - 12x - x + 3 ( factor the first/second and third/fourth terms )

= 4x(x - 3) - 1(x - 3) ← factor out (x - 3) from each term

= (x - 3)(4x - 1)

Thus

4x² - 13x + 3 = (4x - 1)(x - 3) → D